حساب معامل الانكسار للنفوط المكمنية للتنبؤ بالضغوط المكمنية التي يحدث عندها ترسب الاسفلتينات - الهيد علياء كامل; رضا سلمى محمد (Journal of Petroleum Research and Studies, 2019)
The aim of this study is to determine the deposition of the asphalt that occurs during the oil production process at reservoir pressures. Finding the two refractive index one for crude oil (STO) and the second for live oil using models and mathematical equations and using the results of physical tests of reservoir oil (PVT).Asphalt is a part of heavy sections in crude oil and can be polarized during production process. Asphalt is defined based on its solubility in solvents or can be defined at which dissolve in aromatic solvents and do not dissolve in paraffin solvents or is a function of the solubility of asphalt in crude oil. Most of the world’s oil fields suffer from the problem of deposition of asphalt that accompanies the process of production of crude oil in all stage from the area near the opening of the well, tubing pipe, surface equipment, transport pipes, and even reservoirs, causing many problems such as damage to the oil reservoir .In addition it case blockages in production pipes, conveyor lines and equipment. Many companies in the world have studied this problem through many methods and models to understand the conditions of deposition of asphalt and its causes to find appropriate solutions. The most important reasons for the deposition of asphalt are the changes in the pressure and temperature and components of crude oil during the production process and electrostatic shear stresses. The northern region (Kirkuk, Khabaz, Jambur) suffers from the problem of asphalt deposition, which causes, blockage in the pipes and production equipment where they are treated by cleaning the clogged parts with solvents and mechanical processes, and this requires efforts, time and cases losses in production. The aim of this paper is to identify the problem, and find solutions for it, and appropriate treatment methods, methods of predicting the problem, and avoiding or hindering it. In determining the reservoir pressures at which the deposition of the asphalt in the oil production process occurs with the refractive index of the crude oil, the problem can be solved and the optimal solution of the deposition can be achieved by using several solvents to dissolve the asphalt deposits of the wells. Toluene is a substance that can be used with its own safety measures (toluene is a volatile light substance).It is also preferred to use the technique of coiled tube, in the absence of toluene it is possible to use kerosene reformate white elite.